2005
DOI: 10.1007/s00425-005-0103-1
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific phosphorylation of L-form starch phosphorylase by the protein kinase activity from sweet potato roots

Abstract: A 78-amino acid insertion (L78) is found in the low-affinity type (L-form) of starch phosphorylase (L-SP, EC 2.4.1.1). This insertion blocks the starch-binding site on the L-SP molecule, and it decreases the binding affinity of L-SP toward starch. The computational analysis of the amino acid sequence on L78 predicts several phosphorylation sites at its Ser residues. Indeed, from the immunoblotting results using antibodies against phosphoamino acids, we observed that the purified L-SP from mature sweet potato (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 41 publications
1
31
1
Order By: Relevance
“…4B). Although OsDpe1 co-eluted with OsPho1 in a small range of high molecular weight fractions (fractions [11][12][13][14], OsPho1 proteins were detected in a broader range of fractions (10 -18) with the latter fractions overlapping with the elution profile of ␤-amylase (200 kDa) that was used as a molecular size marker. When a protein extract from immature seeds of BMF136 (pho1 null mutant) was analyzed, OsDpe1 proteins were no longer eluted in the high molecular weight fractions but, instead, were FIGURE 2.…”
Section: Native Osdpe1 Is Eluted As a High Molecular Weight-tomentioning
confidence: 99%
See 1 more Smart Citation
“…4B). Although OsDpe1 co-eluted with OsPho1 in a small range of high molecular weight fractions (fractions [11][12][13][14], OsPho1 proteins were detected in a broader range of fractions (10 -18) with the latter fractions overlapping with the elution profile of ␤-amylase (200 kDa) that was used as a molecular size marker. When a protein extract from immature seeds of BMF136 (pho1 null mutant) was analyzed, OsDpe1 proteins were no longer eluted in the high molecular weight fractions but, instead, were FIGURE 2.…”
Section: Native Osdpe1 Is Eluted As a High Molecular Weight-tomentioning
confidence: 99%
“…In sweet potato roots, high molecular weight complexes showing Pho1 activity contained the 20S proteasome that interacts with the L78 region of Pho1 and degrades the Pho1 protein under heat stress (10). In addition, like the L80 of OsPho1 the L78 of sweet potato, Pho1 has a number of charged amino acids that have been suggested to be potential targets for protein kinase activity (11). It was proposed that L78 serves as a switch controlling the catalytic direction of the enzyme reaction as proteolytic removal of the L78 region induced by the phosphorylation event resulted in alteration of the enzyme's affinities toward substrates (8).…”
mentioning
confidence: 99%
“…The L78 region of PHO1 represents a large insertion that is typical for PHO1 in plastids of higher plants, but is not observed in the cytosolic isozyme nor in the well-studied glycogen phosphorylase. Surprisingly, five of the phosphorylation sites identified by Walley et al (2013) within L78 appear to be specific to cereals and not found in dicots such as sweet potato where other phosphorylation sites were identified (Young et al 2006), whereas the sixth site is conserved amongst all species homologues of PHO1 (Table 8.2). It is tempting to speculate that the hyperphosphorylated acidic region of PHO1 plays a distinctive role in the regulation of starch biosynthesis in the developing seeds of monocots, though any function would be conjecture at this stage.…”
Section: Regulation Of Protein Complex Formation By Protein Phosphorymentioning
confidence: 90%
“…The concentration of total protein was also quantitated using the BCA protein assay reagent (Pierce Biotechnology) as previously described [15,18,19]. For 2DE-DIGE analysis, 50 μg of total protein from the control group was mixed with 400 pmol of CyDye (Cy3; GE Healthcare, Piscataway, NJ) and either the adenine or AICAR-stimulated group was labeled with CyDye (Cy5; GE Healthcare), respectively.…”
Section: Proteomic Methodsmentioning
confidence: 99%